Pengaruh Kepuasan Kerja, Dan Komitmen Organisasional Terhadap Kinerja Karyawan Yang Dimoderasi Oleh Motivasi Kerja Di Yayasan Wakaf Darussalam Subah - Inka Nuromavita (Fakultas Ekonomika dan Bisnis Universitas Selamat Sri, 2023)
In the current era of globalization, the challenges of rapid environmental change and the advancement of information technology that the organization's sensitivity in response to changes that occur in order to remain exist and productive. The reason of the problem in this research is